Cyclic Silylselenides: Convenient Selenium Precursors for Atomic Layer Deposition - Charvot, Jaroslav; Pokorný, Daniel; Zazpe, Raul; Krumpolec, Richard; Pavliňák, David; Hromádko, Luděk; Přikryl, Jan; Rodriguez Pereira, Jhonatan; Klikar, Milan; Jelínková, Veronika; Macák, Jan; Bureš, Filip (Wiley-VCH, 2020)
Three cyclic silylselenides were prepared in a straightforward manner. Property tuning has been achieved by varying the ring size and the number of embedded selenium atoms. All silylselenides possess improved resistance towards moisture and oxidation as well as high thermal robustness and sufficient volatility with almost zero residues. The six-membered diselenide proved to be particularly superior Se precursors for atomic layer deposition and allowed facile preparation of MoSe2 layers. Their structure and composition have been investigated by Raman and X-ray photoelectron spectroscopy as well as scanning electron microscopy revealing vertically aligned flaky shaped nanosheets.
Cyklické silylselenidy: Pohodlné prekurzory selenu pro depozici atomových vrstev.
Keywords: atomic layer deposition; molybdenum; nanostructures; selenium; transition metal dichalcogenides; cyklické silylselenidy; nanostruktury; molybden; selen; depozice atomových vrstev